Challenges of Resource Description and Access (RDA) Implementation in Sub-Saharan Africa: A Review of Literature. Issue 2 (2nd July 2020) - Monyela, Madireng
Abstract: Resource Description and Access (RDA) is a new cataloguing standard, designed for the digital world, built on foundations established by Anglo American Cataloguing Rules (AACR) and it is to replace the existing Anglo American Cataloguing Rules, 2 nd Edition (AACR2). RDA provides a comprehensive set of guidelines and instructions on resource description and access covering all types of content and media. It is based on the Functional Requirements for Bibliographic Records (FRBR) in order to relate the user task of retrieval and access in an online library catalogue and biographic database from a user's perspective. Bibliographic records in RDA are more relevant in an online environment by enabling catalogs to cluster related records to show different manifestations of the same work. Patrons could discover that the information sources they are seeking are available in different forms in the library. This paper investigated RDA as a new standard for cataloguing as well as the challenges related to RDA implementation in libraries in Sub-Saharan Africa, as the literature evidence that many libraries in Africa are still using the AACR. Qualitative research approach based on document content analysis was used. Findings revealed that RDA is gradually implemented in Sub-Saharan Africa however, there are challenges related to power supply, internet connectivity, ICT skills, training, funding and LIS systems. The study recommends alternative power supply, other training options, development of consortia, among others.